PARTISIPASI MASYARAKAT DALAM PEMBENTUKAN PERUNDANG-UNDANGAN UNTUK MEWUJUDKAN KESEJAHTERAAN - Riskiyono, Joko (Jurnal Aspirasi, 2015)
As the law state, Indonesia has the objective to create common prosperity for all Indonesian citizens without exception. To reach these goals it requires policy in the form of legislation product. The House of Representatives (DPR), the Regional Representatives Council (DPD), and the Government should involve community in the process of composing legislation, and similarly at the time of its implementation and monitoring. Therefore the goal of establishing legislation for common prosperity can be achieved. This study aims to reveal the aspirations of the people in the preparation of the National Legislation Program (Prolegnas), the role of community participation in the process of legislation, and to see how the state has involve community in the implementation and supervision of the law. The results showed that the DPR, DPD, and the Government have not considered the aspiration of the people in carrying out their legislative functions.